Election Uncertainty, Economic Policy Uncertainty: An Event Study Approach - Arni Utamaningsih (Journal Research of Social Science, Economics, and Management, 2023)
This study aims to analyze the impact of election uncertainty and economic policy uncertainty on stock market performance in Indonesia using an event study approach. Data obtained from the Indonesia Stock Exchange and the Central Bureau of Statistics during the 2010-2021 period. This study uses the OLS regression model and event study analysis to measure the impact of stock market performance on significant events related to election uncertainty and economic policies. The research results show that the uncertainty of the election and economic policies significantly affect the performance of the stock market in Indonesia. The impact is visible in the period before, during and after the significant events related to the uncertainty. In addition, the results of the analysis also show that elections and more stable economic policies tend to have a positive impact on stock market performance. In conclusion, this study shows that election uncertainty and economic policies have a significant impact on stock market performance in Indonesia. Therefore, it is important for investors to pay attention to political and economic conditions in making their investment decisions.